A polyamide membrane material based on g-bsa loose agglomerates and a method for preparing the same
Patent Information
- Application Number
- CN202611486265.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]为解决现有技术无法有效构建一种既有交联稳定性、又保留疏松空间的蛋白团聚体,使其在PIP/TMC界面聚合时抑制PIP局部瞬时通量峰值、改善PIP在膜面上的空间分布,并由此形成有利于水和无机盐通过、同时对抗生素高截留的分离层等问题,本发明提供了一种基于G-BSA疏松团聚体的聚酰胺膜材料及其制备方法
1)本发明通过先交联戊二醛与牛血清蛋白形成G-BSA疏松团聚体,再引入哌嗪,可抑制哌嗪向油水界面的局部瞬时通量峰值,减弱界面聚合中的突发反应及局部过度致密化,使聚酰胺选择层形成过程更稳定;
Smart Images

Figure CN122999008A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of membrane separation materials and water treatment technology, specifically relating to a polyamide membrane material based on G-BSA loose aggregates and its preparation method. Background Technology
[0002] Wastewater from antibiotic production, pharmaceutical processes, and some aquaculture often contains antibiotic molecules, inorganic salts such as sodium chloride, and other small molecule components. For these systems, if the treatment process only aims for a high organic matter rejection rate while retaining a large amount of inorganic salts, the osmotic pressure across the membrane will rise rapidly, affecting subsequent concentration and continuous operation. Conversely, if the membrane layer is made too porous to allow salt to pass through, antibiotic rejection will be compromised. Therefore, the technical challenge for this type of membrane material is not simply improving a single performance indicator, but rather balancing high antibiotic rejection, low inorganic salt rejection, and high water transport capacity within the same selective layer.
[0003] Interfacial polymerization using piperazine (PIP) as the aqueous monomer and 1,3,5-benzenetricarboxylic acid chloride (TMC) as the oil monomer is a common route for preparing polyamide nanofiltration selective layers. While the rapid interfacial polymerization facilitates quick film formation, it also presents a challenge: when the local PIP flux is excessively high within a short period, concentrated and sudden reactions occur at the interface, leading to overly tight localized accumulation of polyamide segments. Furthermore, when the PIP supply is insufficiently continuous or unevenly distributed, different regions of the membrane will exhibit significantly different crosslinking and transport structures. Therefore, rationally controlling the interfacial reaction process is an effective approach and key to improving the high water transport and selectivity of polyamide nanofiltration membranes.
[0004] Existing methods for regulating performance include altering monomer concentration, reaction time, solvent composition, or adding nanoparticles, hydrophilic polymers, and biomacromolecules. For example, in the preparation of nanofiltration membranes using PIP and TMC interfacial polymerization, the effects of PIP concentration, TMC concentration, aqueous phase treatment time, and organic phase reaction time on membrane performance were investigated. The results showed that these parameters can significantly influence the water flux and salt rejection performance of the membrane by changing the interfacial polymerization process and the polyamide layer structure. Other existing technologies introduce a co-solvent into the PIP / TMC interfacial polymerization system to regulate the interfacial polymerization process by changing the organic phase environment and the transphase diffusion behavior of PIP, and further alter the pore structure and ion separation performance of the polyamide layer.
[0005] The methods described above can regulate the formation process of polyamide selective layers from different perspectives, but they are still mainly controlled by changing the overall reaction conditions or the monomer transphase transport state. Simply changing the concentration of PIP or TMC and the reaction time usually changes the film thickness, crosslinking degree, and overall mass transfer resistance simultaneously, but lacks further spatial regulation of the local instantaneous transport state of PIP in different regions of the film surface. Although using a co-solvent can change the interfacial properties and the transphase diffusion of PIP, its regulation still mainly depends on the solvent environment itself. For schemes that incorporate nanoparticles, hydrophilic polymers, and biomacromolecules, the regulation effect is also affected by factors such as particle dispersion state, polymer conformation, and aggregation state. Therefore, it is still necessary to further study how to pre-form a relatively stable regulatory unit with a certain amount of loose space before the start of interfacial polymerization, and use this structure to further regulate the local migration and spatial distribution of PIP. Summary of the Invention
[0006] To address the limitations of existing technologies in effectively constructing a protein aggregate that possesses both cross-linking stability and retains a loose spatial structure, thereby suppressing local transient flux peaks of PIP during PIP / TMC interface polymerization, improving the spatial distribution of PIP on the membrane surface, and forming a separation layer that facilitates the passage of water and inorganic salts while maintaining high antibiotic retention, this invention provides a polyamide membrane material based on G-BSA loose aggregates and its preparation method.
[0007] The main objective of this invention is: I. A method for controlling interfacial aggregation is provided, which enables PIP to coexist with a stable loose spatial structure before reaching the oil-water interface, thereby reducing the impact of local sudden diffusion and excessively rapid local reactions; Second, without relying on rigid inorganic fillers, the steric hindrance, polar interaction, and cross-linking network of G-BSA loose aggregates are used to adjust the chain segment stacking, free volume, and transport channel connection mode of the polyamide layer to a state that is more conducive to the selective separation of antibiotics and / or salts.
[0008] To achieve the above objectives, the present invention adopts the following technical solution.
[0009] A method for preparing polyamide film materials based on G-BSA loose aggregates. The method includes: 1) Add glutaraldehyde and bovine serum albumin to an alcohol-water solution and mix with ultrasound to obtain a base solution. Then add piperazine to the base solution and continue to sonicate to obtain an aqueous phase mixture. 2) The base membrane is brought into contact with and wetted by the aqueous phase mixture, and excess aqueous phase mixture on the surface is removed to obtain the precursor membrane; 3) The surface of the precursor membrane treated in step 2) is brought into contact with a 1,3,5-benzenetriformyl chloride solution for interfacial polymerization. After heat treatment and cleaning, a polyamide membrane material based on G-BSA loose aggregates is obtained.
[0010] As a preferred option Step 1) The alcohol-water solution is a mixed solution of ethanol and water, wherein the volume ratio of ethanol to water is 1:(2-3). Step 1) The glutaraldehyde concentration in the base solution is 0.1–0.4 wt%, and the bovine serum albumin concentration is 0.1–1.0 wt%. Step 1) The ultrasonic mixing lasts for 5 to 10 minutes.
[0011] As a preferred option Step 1) The ultrasonic treatment lasts for 1 to 5 minutes, and the concentration of piperazine in the aqueous phase mixture obtained after treatment is 0.1 to 0.3 wt%.
[0012] As a preferred option Step 2) The base membrane is a porous polymer base membrane containing amide bonds and / or carbon-fluorine bonds, and its average pore size is 0.1 to 0.22 μm; Step 2) When the basement membrane and the aqueous mixture react, they are in continuous contact for 3 to 10 minutes, while at least one side of the basement membrane is completely covered by the aqueous mixture.
[0013] As a preferred option Step 2) The base membrane is a nylon membrane and / or a polyvinylidene fluoride membrane.
[0014] As a preferred option Step 3) The 1,3,5-benzenetricarboxylic acid chloride solution is a hexane solution of 1,3,5-benzenetricarboxylic acid chloride, wherein the concentration of 1,3,5-benzenetricarboxylic acid chloride is 0.1–0.3 wt%. Step 3) involves contacting the surface of the precursor film treated in step 2) with a 1,3,5-benzenetriformyl chloride solution for at least 120 s to perform interfacial polymerization.
[0015] As a preferred option Step 3) The heat treatment temperature is controlled at 50-65 ℃, and the treatment time is 10-20 min.
[0016] A polyamide film material based on loose aggregates of G-BSA, The polyamide membrane material based on G-BSA loose aggregates includes a porous polymer base membrane and a polyamide selective layer located on at least one side of the porous polymer base membrane. The G-BSA loose aggregates are loaded on the side before interfacial polymerization and participate in regulating the local transport of piperazine to the oil phase interface.
[0017] As a preferred option The polyamide membrane material is used for the selective separation of antibiotics and / or inorganic salts.
[0018] This invention does not directly mix glutaraldehyde, bovine serum albumin and piperazine. Instead, glutaraldehyde and bovine serum albumin first form a loose G-BSA aggregate, then piperazine is added, and interfacial polymerization is carried out under the control of the loose G-BSA aggregate.
[0019] Here, G-BSA refers to a cross-linked aggregate formed by glutaraldehyde and bovine serum albumin, where G represents glutaraldehyde and BSA represents bovine serum albumin.
[0020] The aldehyde group in glutaraldehyde can condense with active groups such as amino groups in bovine serum albumin (BSA) to form a cross-linked structure. Under the influence of alcohol and water and ultrasound, BSA remains dispersed and forms a relatively stable spatial network through cross-linking with glutaraldehyde.
[0021] The network is not a completely dense gel structure, but a loose aggregated structure that retains internal pores and segmental spacing.
[0022] The amounts of glutaraldehyde and bovine serum albumin together affect the formation and cross-linking state of G-BSA aggregates: when the degree of cross-linking is low, the aggregate structure is less stable; when the degree of cross-linking is too high or the protein content is too high, the aggregate size may increase or the local structure may become denser.
[0023] Therefore, the regulatory effect of G-BSA on interfacial polymerization does not increase monotonically with the increase of aggregation scale or cross-linking degree, but is related to the matching relationship between structural stability and porosity.
[0024] Based on this, after adding piperazine to the base solution, piperazine can be distributed in the continuous aqueous phase and the aqueous phase region surrounding the G-BSA aggregates. Polar groups such as hydroxyl, amino, carboxyl, and amide groups in bovine serum albumin may affect the local distribution of piperazine and water molecules through hydrogen bonding and dipole interactions. In addition, the steric hindrance and three-dimensional network structure of G-BSA may also change the migration path of piperazine from the bulk aqueous phase to the water-oil interface. Therefore, the regulatory effect of G-BSA aggregates on piperazine transport is not manifested as a unidirectional increase or decrease in the overall diffusion rate of piperazine. Its main role is more likely to suppress the local instantaneous flux peak caused by short-term concentration of piperazine at the interface, and promote a more uniform spatial distribution of piperazine near the interface.
[0025] When the precursor membrane comes into contact with a 1,3,5-benzenetricarboxyl chloride solution, piperazine migrates from the aqueous phase to the oil-water interface and is affected by the spatial structure of the loose aggregates of G-BSA, and then polymerizes with 1,3,5-benzenetricarboxyl chloride.
[0026] The spatial hindrance and polar interactions formed by G-BSA may regulate the local migration and spatial distribution of piperazine, reducing the possibility of excessively rapid reaction rates in local areas due to excessively high instantaneous piperazine flux, and decreasing the likelihood of low-crosslinking regions forming in other areas due to insufficient local piperazine supply. Therefore, the resulting polyamide selective layer can reduce localized excessively dense packing and non-uniform structures, and is conducive to the formation of a more uniform crosslinking and transport structure.
[0027] During the formation of the polyamide selective layer, the space formed by G-BSA aggregates, the interface region between G-BSA aggregates and polyamide segments, and their steric hindrance effect on polyamide segments may all inhibit the excessive compaction of local polyamide segments. This is beneficial for retaining a certain effective free volume inside the selective layer and forming more nanoscale transport channels with certain connectivity.
[0028] During the separation process, water molecules can migrate through polar sites and interconnected transport channels in the selective layer. Inorganic salt ions, with their smaller hydration size, also exhibit high permeability when the transport path scale and local structure are suitable. Antibiotic molecules typically have larger molecular sizes and more complex spatial configurations, and may interact with the polyamide layer and protein-associated sites, thus limiting their transport in the selective layer. Therefore, the polyamide layer regulated by G-BSA can possess a more suitable transport structure, which is beneficial for maintaining a high antibiotic rejection rate while reducing inorganic salt rejection and increasing water transport capacity, thereby improving the selective separation of antibiotics and salts.
[0029] Thus, this invention embodies a continuous regulatory relationship, from the synergistic regulation of G-BSA aggregate structure, piperazine transport behavior and interfacial polymerization process, to the adjustment of polyamide selective layer transport structure, and then to the improvement of selective separation of antibiotics and inorganic salts.
[0030] The beneficial effects of this invention are as follows: 1) This invention first crosslinks glutaraldehyde with bovine serum albumin to form loose G-BSA aggregates, and then introduces piperazine, which can suppress the local instantaneous flux peak of piperazine to the oil-water interface, weaken the sudden reaction and local over-densification in the interfacial polymerization, and make the polyamide selective layer formation process more stable. 2) The steric hindrance, polarity, and cross-linking network of G-BSA can regulate the polyamide segment stacking, free volume, and nanochannel connectivity; 3) The method of the present invention does not rely on rigid inorganic fillers, the preparation conditions are mild, and it can be used for nylon membranes and polyvinylidene fluoride membranes, which is beneficial to obtaining composite membranes with high antibiotic rejection, high salt permeability and rapid water transport capabilities. Attached Figure Description
[0031] Figure 1 This is a scanning electron micrograph of the polyamide film material based on G-BSA loose aggregates prepared in Example 1; Figure 2 Scanning electron micrograph of the polyamide membrane material prepared in Comparative Example 1 without the addition of glutaraldehyde and bovine serum albumin; Figure 3 The image shows a scanning electron microscope image of the polyamide membrane material prepared in Comparative Example 2 with only bovine serum albumin added. Figure 4 The image shows a scanning electron microscope image of the polyamide film material with only glutaraldehyde added, prepared in Comparative Example 3. Figure 5 This is a transmission electron micrograph of the loose G-BSA aggregates formed by glutaraldehyde and bovine serum albumin in Example 1. Detailed Implementation
[0032] The present invention will be further described clearly and in detail below with reference to specific embodiments and the accompanying drawings. Those skilled in the art will be able to implement the present invention based on these descriptions. Furthermore, the embodiments of the present invention described below are generally only some, not all, of the embodiments of the present invention. Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort should fall within the scope of protection of the present invention.
[0033] Unless otherwise specified, all raw materials used in the embodiments of this invention are commercially available products, and all testing and characterization methods employed are conventional methods in the art. G-BSA, as referred to herein, refers to the loose cross-linked aggregates formed by glutaraldehyde and bovine serum albumin before the addition of piperazine. The nylon membrane and polyvinylidene fluoride membrane used in the embodiments of this invention were purchased from Jinteng, and both membranes have a diameter of 50 mm and a pore size of 0.22 μm.
[0034] Before conducting separation performance tests, the membrane material was first filtered with pure water until the water flux remained stable. Then, a cross-flow filtration method was used, with pressure as the driving force, to test the water transport performance and the separation performance of antibiotics and inorganic salts. Performance data given in each embodiment and comparative example were obtained according to the temperature, transmembrane pressure, and feed concentration specified in the corresponding paragraphs. Tetracycline hydrochloride concentration was determined by changes in absorbance, and NaCl concentration was determined by changes in solution conductivity. The rejection rate R was calculated as R = [1 - (Cp / Cf)] × 100%, where Cf is the concentration of the analyte in the feed solution, and Cp is the concentration of the analyte in the permeate. Water flux J was calculated as J = V / (A × ΔP × t), where V is the permeate volume, A is the effective membrane area, ΔP is the transmembrane pressure, and t is the operating time. The unit of water flux is L·m³. -2 ·h -1 ·bar -1 .
[0035] The surface and cross-sectional morphology of the membrane material were observed using scanning electron microscopy, while the morphology of the loose aggregates of G-BSA was observed using transmission electron microscopy.
[0036] Example 1
[0037] A method for preparing polyamide film materials based on G-BSA loose aggregates. Please follow these steps: Step 1) Prepare an alcohol-water solution with a volume ratio of ethanol to water of 2:5. Add glutaraldehyde and bovine serum albumin to the alcohol-water solution and sonicate for 6 min to form loose G-BSA aggregates with glutaraldehyde and bovine serum albumin to obtain the base solution. Then piperazine was added to the base solution, and ultrasonic treatment was continued for 2 min to ensure uniform dispersion of piperazine, resulting in an aqueous mixture. The resulting aqueous mixture contained 0.3 wt% glutaraldehyde, 0.5 wt% bovine serum albumin, and 0.2 wt% piperazine.
[0038] Step 2) Select a nylon membrane with a diameter of 50 mm and a pore size of 0.22 μm as a porous polymer base membrane, and make one side surface of the base membrane fully contact the aqueous phase mixture obtained in Step 1), and keep the side surface completely covered by the aqueous phase mixture for 5 min. Subsequently, excess aqueous phase mixture was removed from the surface of the basement membrane to obtain the precursor membrane; Step 3) The side of the precursor membrane obtained in Step 2) that has been treated with an aqueous mixture is contacted with a 0.2 wt% hexane solution of 1,3,5-benzenetricarboxylic acid chloride for 120 s to allow piperazine and 1,3,5-benzenetricarboxylic acid chloride to undergo interfacial polymerization. After the reaction, the material was heat-treated at 60 °C for 15 min and then washed with water to obtain the target product, a polyamide membrane material based on G-BSA loose aggregates.
[0039] The obtained membrane material was tested at 25 °C and 4 bar, showing a retention rate of 99.70% for 20 mg / L tetracycline hydrochloride and 11.23% for 0.5 g / L NaCl aqueous solution, with a water flux of 24.40 L·m⁻¹. -2 ·h -1 ·bar -1 .
[0040] Performance test results show that this embodiment maintains a high tetracycline hydrochloride rejection rate while also having a low NaCl rejection rate and a high water flux, demonstrating good selective separation performance of antibiotics / inorganic salts.
[0041] like Figure 1 As shown, the surface of the obtained membrane material is generally smooth with a relatively uniform dotted structure, and the thickness of the polyamide selective layer is approximately 111 nm. Combined with... Figure 5 It is known that glutaraldehyde forms an aggregated structure with a loose outline and internal space with bovine serum albumin. Notably, despite a selective layer thickness of approximately 111 nm, the water flux remains at a high level, indicating that membrane thickness is not the only factor determining transport performance. Its transport performance may also be related to the regulation of polyamide segment stacking state, effective free volume, and channel connectivity by G-BSA.
[0042] Comparative Example 1 The preparation steps of this comparative example are basically the same as those of Example 1, except that glutaraldehyde and bovine serum albumin are not added in step 1), that is, no loose G-BSA aggregates are formed in the aqueous phase. The other preparation and testing conditions remain unchanged.
[0043] The obtained membrane material, under conditions of 25 °C and 4 bar, exhibited a retention rate of 99.10% for 20 mg / L tetracycline hydrochloride and 26.67% for 0.5 g / L NaCl aqueous solution, with a water flux of 8.56 L·m⁻¹. -2 ·h -1 ·bar -1 .
[0044] Compared with Example 1, this comparative example still has a high rejection rate for tetracycline hydrochloride, but the NaCl rejection rate is significantly increased, while the water flux is significantly reduced.
[0045] The above results indicate that, in the absence of G-BSA regulation, the resulting polyamide layer still has a certain antibiotic retention capacity, but it has a large resistance to the transport of salt and water, and the antibiotics and salts are not selectively separated.
[0046] like Figure 2 As shown, noticeable irregular bulges can be observed on the surface of the membrane obtained in this comparative example. This morphological feature may be related to uneven local piperazine transport and differences in interfacial polymerization rates. The selective layer thickness is approximately 65 nm, which is thinner than the approximately 111 nm of Example 1, but the water flux is lower than that of Example 1.
[0047] The above results indicate that a reduction in the selective layer thickness does not necessarily correspond to higher water transport performance. In the absence of G-BSA regulation, polyamide segments may form a relatively non-uniform and locally compact structure, thereby increasing the resistance to transmembrane transport of water molecules.
[0048] Comparative Example 2 The preparation steps of this comparative example are basically the same as those of Example 1, except that glutaraldehyde is not added in step 1), that is, the aqueous phase contains bovine serum albumin but does not form glutaraldehyde-crosslinked loose aggregates of G-BSA. The other preparation and testing conditions remain unchanged.
[0049] The obtained membrane material, under conditions of 25 °C and 4 bar, exhibited a retention rate of 94.76% for 20 mg / L tetracycline hydrochloride and 16.33% for 0.5 g / L NaCl aqueous solution, with a water flux of 11.36 L·m⁻¹. -2 ·h -1 ·bar -1 .
[0050] Compared to Example 1, the tetracycline hydrochloride rejection rate and water flux of this comparative example were reduced. The addition of bovine serum albumin alone failed to achieve an interfacial polymerization regulation effect comparable to that of G-BSA, possibly because bovine serum albumin without glutaraldehyde cross-linking lacks a relatively stable spatial network structure. Its regulatory effect on the local transport of piperazine during interfacial polymerization is relatively limited, and it may be difficult to maintain a relatively stable loose spatial structure.
[0051] like Figure 3 As shown, the membrane surface obtained in this comparative example exhibits an irregular bulging structure, with a selective layer thickness of approximately 135 nm. These results further indicate that the performance regulation of this invention does not solely depend on increasing or decreasing the selective layer thickness, but is likely primarily related to the regulation of the chain segment stacking and transport structure within the selective layer by the cross-linked protein aggregation structure.
[0052] Comparative Example 3 The preparation steps of this comparative example are basically the same as those of Example 1, except that bovine serum albumin is not added in step 1), that is, the aqueous phase contains glutaraldehyde but does not form loose G-BSA aggregates supported by bovine serum albumin. The other preparation and testing conditions remain unchanged.
[0053] The obtained membrane material, under conditions of 25 °C and 4 bar, exhibited a retention rate of 93.76% for 20 mg / L tetracycline hydrochloride and 14.16% for 0.5 g / L NaCl aqueous solution, with a water flux of 12.33 L·m⁻¹. -2 ·h -1 ·bar -1 .
[0054] The tetracycline hydrochloride rejection rate and water flux in this comparative example were also lower than those in Example 1, indicating that the introduction of glutaraldehyde alone is unlikely to achieve a regulatory effect comparable to that of loose G-BSA aggregates. Glutaraldehyde is a small molecule cross-linking agent, and without bovine serum albumin to provide a macromolecular scaffold, it is difficult to form a stable sterically hindered aggregate network on its own.
[0055] like Figure 4 As shown, the surface of the comparative example membrane exhibits an irregular wrinkled structure, and the selective layer thickness is approximately 53 nm. Combining the results of Comparative Examples 1 and 2, it can be seen that the effect of this invention is not solely due to either glutaraldehyde or bovine serum albumin, but rather related to the pre-formation of cross-linked aggregates with certain stability and loose characteristics.
[0056] Example 2
[0057] Steps 1) and 3) of this embodiment are the same as those of embodiment 1; in step 2), the base membrane is replaced with a polyvinylidene fluoride membrane with a diameter of 50 mm and a pore size of 0.22 μm, the contact time of the aqueous phase mixture is still 5 min, and the other preparation and testing conditions remain unchanged.
[0058] The obtained membrane material, under conditions of 25 °C and 4 bar, exhibited a retention rate of 98.51% for 20 mg / L tetracycline hydrochloride and a retention rate of 12.50% for 0.5 g / L NaCl aqueous solution, with a water flux of 20.14 L·m⁻¹. -2 ·h -1 ·bar -1 .
[0059] In this embodiment, only the substrate membrane material was changed, and the resulting membrane material still exhibited a high tetracycline hydrochloride rejection rate, a low NaCl rejection rate, and a high water flux. These results indicate that the regulatory effect of G-BSA on interfacial polymerization is not limited to nylon substrates but is also applicable to polyvinylidene fluoride substrates. The separation performance of composite membranes obtained from different substrate membranes may vary, which may be related to the influence of the substrate surface chemical properties and the aqueous phase loading state on the subsequent polyamide layer formation process.
[0060] Example 3
[0061] The preparation steps in this embodiment are the same as in Example 1, except that the concentration of bovine serum albumin in the aqueous mixture obtained in step 1) is adjusted to 0.1 wt%, the concentration of glutaraldehyde remains 0.3 wt%, and the concentration of piperazine remains 0.2 wt%, while the other preparation and testing conditions remain unchanged.
[0062] The obtained membrane material, under conditions of 25 °C and 4 bar, exhibited a retention rate of 99.40% for 20 mg / L tetracycline hydrochloride and 13.66% for 0.5 g / L NaCl aqueous solution, with a water flux of 21.93 L·m⁻¹. -2 ·h -1 ·bar -1 .
[0063] Even with reduced bovine serum albumin (BSA) concentration, the resulting membrane material still exhibited good antibiotic / salt-selective separation performance. Compared to Example 1 with a BSA concentration of 0.5 wt%, the water flux and NaCl rejection rate in this example were slightly lower, indicating that the G-BSA structure formed at lower BSA concentrations had a relatively weaker regulatory effect on interfacial polymerization and transport structure, and may not yet have achieved a optimal balance between structural stability and porosity.
[0064] Example 4
[0065] The preparation steps in this embodiment are the same as in Example 1, except that the concentration of bovine serum albumin in the aqueous mixture obtained in step 1) is adjusted to 1.0 wt%, the concentration of glutaraldehyde remains 0.3 wt%, and the concentration of piperazine remains 0.2 wt%, while the other preparation and testing conditions remain unchanged.
[0066] The obtained membrane material, under conditions of 25 °C and 4 bar, exhibited a retention rate of 97.16% for 20 mg / L tetracycline hydrochloride and 10.76% for 0.5 g / L NaCl aqueous solution, with a water flux of 14.30 L·m⁻¹. -2 ·h -1 ·bar -1 .
[0067] Comparing Examples 3, 1, and this example based on bovine serum albumin (BSA) concentration reveals that the overall separation performance of the membrane material does not continuously improve with increasing BSA concentration. Even after increasing BSA to 1.0 wt%, the NaCl rejection rate remains low, but the water flux decreases significantly, and the tetracycline hydrochloride rejection rate also decreases. When the BSA content further increases, the number, size, or local aggregation degree of G-BSA aggregates may increase, thereby increasing water transport resistance and affecting the uniform formation of the polyamide selective layer.
[0068] Example 5
[0069] The preparation steps in this embodiment are the same as in Example 1, except that the concentration of glutaraldehyde in the aqueous mixture obtained in step 1) is adjusted to 0.1 wt%, the concentration of bovine serum albumin is still 0.5 wt%, and the concentration of piperazine is still 0.2 wt%, while the other preparation and testing conditions remain unchanged.
[0070] The obtained membrane material, under conditions of 25 °C and 4 bar, exhibited a retention rate of 99.44% for 20 mg / L tetracycline hydrochloride and 11.77% for 0.5 g / L NaCl aqueous solution, with a water flux of 13.88 L·m⁻¹. -2 ·h -1 ·bar -1 .
[0071] This embodiment exhibits good selective separation performance of tetracycline hydrochloride / sodium chloride, but the water flux is relatively low. These results suggest that at lower glutaraldehyde concentrations, the formation of loose G-BSA aggregates may be limited, and the integrity and stability of the resulting crosslinked network may be relatively low, thus limiting its ability to regulate the selective layer transport structure.
[0072] Example 6
[0073] The preparation steps in this embodiment are the same as in Example 1, except that the concentration of glutaraldehyde in the aqueous mixture obtained in step 1) is adjusted to 0.2 wt%, the concentration of bovine serum albumin is still 0.5 wt%, and the concentration of piperazine is still 0.2 wt%, while the other preparation and testing conditions remain unchanged.
[0074] The obtained membrane material, under conditions of 25 °C and 4 bar, exhibited a retention rate of 99.45% for 20 mg / L tetracycline hydrochloride, a retention rate of 17.46% for 0.5 g / L NaCl aqueous solution, and a water flux of 17.47 L·m⁻¹. -2 ·h -1 ·bar -1 .
[0075] Compared to Example 5, increasing the glutaraldehyde concentration from 0.1 wt% to 0.2 wt% resulted in an increase in water flux, but also an increase in NaCl rejection. These results indicate that changes in glutaraldehyde concentration may simultaneously affect the cross-linking state of G-BSA aggregates and the subsequent interfacial polymerization process. Different separation performance indicators may exhibit asynchronous changes; therefore, a comprehensive evaluation of the balance between antibiotic rejection, salt permeation, and water flux is necessary.
[0076] Example 7
[0077] The preparation steps in this embodiment are the same as in Example 1, except that the concentration of glutaraldehyde in the aqueous mixture obtained in step 1) is adjusted to 0.4 wt%, the concentration of bovine serum albumin is still 0.5 wt%, and the concentration of piperazine is still 0.2 wt%, while the other preparation and testing conditions remain unchanged.
[0078] The obtained membrane material, under conditions of 25 °C and 4 bar, exhibited a retention rate of 95.47% for 20 mg / L tetracycline hydrochloride and 11.23% for 0.5 g / L NaCl aqueous solution, with a water flux of 25.10 L·m⁻¹. -2 ·h -1 ·bar -1 .
[0079] This embodiment demonstrates a high water flux compared to other embodiments, while the NaCl rejection rate remains low, although the tetracycline hydrochloride rejection rate decreases to 95.47%. These results indicate that increasing the glutaraldehyde concentration further improves water transport performance, but a certain balance exists between water transport performance and antibiotic rejection performance.
[0080] Based on the above examples and comparative examples, it is evident that: First, glutaraldehyde and bovine serum albumin (BSA) need to participate together and pre-form loose G-BSA aggregates; introducing either component alone did not yield comparable overall separation performance. Second, higher concentrations of G-BSA-related components do not necessarily improve overall separation performance; both BSA and glutaraldehyde concentrations can affect crosslinking stability, spatial looseness, and subsequent interfacial polymerization. Furthermore, considering the correlation between membrane morphology and separation performance, the performance regulation of this invention does not solely rely on adjusting the selective layer thickness, but may be related to the local transport state of piperazine near the membrane surface, the uniformity of interfacial polymerization, and the connectivity of transport paths within the polyamide layer. These results are consistent with the aforementioned analysis of the mechanism of action of loose G-BSA aggregates and demonstrate that the method of this invention can obtain polyamide membrane materials with selective separation capabilities for antibiotics and inorganic salts.
[0081] Comparative Example 4 In this example, glutaraldehyde, bovine serum albumin, and piperazine were simultaneously added to a mixture of ethanol and water at a volume ratio of 2:5, with the concentrations of glutaraldehyde, bovine serum albumin, and piperazine maintained at 0.3 wt%, 0.5 wt%, and 0.2 wt%, respectively. The mixture was then sonicated for 8 minutes, ensuring the overall sonication time was essentially the same as in Example 1. All other steps and testing conditions were identical to those in Example 1.
[0082] The obtained membrane material, under conditions of 25 °C and 4 bar, exhibited a retention rate of 95.64% for 20 mg / L tetracycline hydrochloride, a retention rate of 15.06% for 0.5 g / L NaCl aqueous solution, and a water flux of 14.46 L·m⁻¹. -2 ·h -1 ·bar -1 .
[0083] Compared with Example 1, the types and final concentrations of the three components in this comparative example are the same. The main difference is that glutaraldehyde and bovine serum albumin did not form loose G-BSA aggregates before piperazine was added. This indicates that the performance improvement of the present invention does not come from the simple coexistence of glutaraldehyde, bovine serum albumin and piperazine.
[0084] When all three are added simultaneously, glutaraldehyde may react or interact with piperazine in the aqueous phase, and may also hinder the formation of a relatively stable loose cross-linked structure of bovine serum albumin. The final system is more likely to form a multi-component co-dispersed aqueous system, rather than a system in which the local migration and spatial distribution of piperazine can be regulated by pre-constructed G-BSA loose aggregates.
[0085] Therefore, this comparative example further illustrates that the addition of piperazine after the formation of G-BSA is not a difference in the order of feeding, but rather a pre-establishment of a control unit with a specific spatial structure before use for interfacial polymerization.
[0086] Comparative Example 5 In this example, glutaraldehyde and bovine serum albumin were added to a mixture of ethanol and water in a volume ratio of 2:5, sonicated for 6 min, and allowed to stand for crosslinking for 60 min before piperazine was added. The mixture was then sonicated for 2 min. The remaining steps and test conditions were the same as in Example 1.
[0087] The obtained membrane material, under conditions of 25 °C and 4 bar, exhibited a retention rate of 98.27% for 20 mg / L tetracycline hydrochloride and 17.47% for 0.5 g / L NaCl aqueous solution, with a water flux of 9.24 L·m⁻¹. -2 ·h -1 ·bar -1 .
[0088] Comparing this comparative example with Example 1 reveals that the concentrations of glutaraldehyde, bovine serum albumin, and piperazine used in both are the same. The main difference lies in the fact that in this comparative example, after ultrasonic mixing of glutaraldehyde and bovine serum albumin, an additional 60-minute static crosslinking period was performed. In Example 1, the tetracycline hydrochloride rejection rate, NaCl rejection rate, and water flux were 99.70%, 11.23%, and 24.40 L·m⁻¹, respectively. -2 ·h -1 ·bar -1 The proportions for these pairs were 98.27%, 17.47%, and 9.24 L·m⁻¹, respectively. -2 ·h -1 ·bar -1 .
[0089] The test results show that this comparative sample still maintains a high tetracycline hydrochloride rejection rate, but the NaCl rejection rate increases, while the water flux decreases significantly. This result indicates that the control effect between glutaraldehyde and bovine serum albumin does not continuously increase with prolonged cross-linking time or degree of cross-linking. Under prolonged cross-linking conditions, the resulting protein aggregate structure may shrink or become locally compacted, thereby reducing the internal space available for water molecules and piperazine to enter, and increasing the tortuosity of the migration path of piperazine from the continuous aqueous phase to the membrane surface.
[0090] In this case, G-BSA can still participate in the subsequent interfacial polymerization process as a cross-linked protein structure. Therefore, the membrane material still maintains a high tetracycline hydrochloride rejection rate. However, its role in the local transport of piperazine may deviate from the more suitable local transport regulation state in Example 1 and may exhibit a strong steric hindrance effect. On the one hand, it will be detrimental to the formation of a more uniform transport structure near the interface. On the other hand, it may also reduce the effective free volume and transport path connectivity between the obtained polyamide segments, thereby resulting in increased water transport resistance and decreased NaCl permeability.
[0091] Therefore, not all glutaraldehyde cross-linked bovine serum albumin with arbitrary structures can achieve the same regulatory effect. Instead, a suitable balance needs to be maintained between cross-linking stability and structural looseness. Insufficient cross-linking makes it difficult to form a stable spatial network, while excessive cross-linking time may increase transport resistance. G-BSA needs to retain appropriate looseness while maintaining a certain level of structural stability to better obtain the comprehensive separation performance of high antibiotic rejection, low NaCl rejection, and high water flux shown in Example 1.
Claims
1. A method for preparing a polyamide film material based on G-BSA loose aggregates, characterized in that, The method includes: Step 1) Add glutaraldehyde and bovine serum albumin to an alcohol-water solution and mix with ultrasound to obtain a base solution. Then add piperazine to the base solution and continue to sonicate to obtain an aqueous phase mixture. Step 2) Wet the base membrane with the aqueous mixture and remove excess aqueous mixture from the surface to obtain the precursor membrane; Step 3) The surface of the precursor membrane treated in step 2) is brought into contact with a 1,3,5-benzenetriformyl chloride solution for interfacial polymerization. After heat treatment and cleaning, a polyamide membrane material based on G-BSA loose aggregates is obtained.
2. The method for preparing a polyamide membrane material based on G-BSA loose aggregates according to claim 1, characterized in that, Step 1) The alcohol-water solution is a mixed solution of ethanol and water, wherein the volume ratio of ethanol to water is 1:(2-3). Step 1) The glutaraldehyde concentration in the base solution is 0.1–0.4 wt%, and the bovine serum albumin concentration is 0.1–1.0 wt%. Step 1) The ultrasonic mixing lasts for 5 to 10 minutes.
3. The method for preparing a polyamide membrane material based on G-BSA loose aggregates according to claim 1 or 2, characterized in that, Step 1) The ultrasonic treatment lasts for 1 to 5 minutes, and the concentration of piperazine in the aqueous mixture obtained after treatment is 0.1 to 0.3 wt%.
4. The method for preparing a polyamide membrane material based on G-BSA loose aggregates according to claim 1, characterized in that, Step 2) The base membrane is a porous polymer base membrane containing amide bonds and / or carbon-fluorine bonds, and its average pore size is 0.1 to 0.22 μm; Step 2) When the basement membrane and the aqueous mixture react, they are in continuous contact for 3 to 10 minutes, while at least one side of the basement membrane is completely covered by the aqueous mixture.
5. A method for preparing a polyamide film material based on G-BSA loose aggregates according to claim 1 or 4, characterized in that, Step 2) The base membrane is a nylon membrane and / or a polyvinylidene fluoride membrane.
6. The method for preparing a polyamide membrane material based on G-BSA loose aggregates according to claim 1, characterized in that, Step 3) The 1,3,5-benzenetricarboxylic acid chloride solution is a hexane solution of 1,3,5-benzenetricarboxylic acid chloride, wherein the concentration of 1,3,5-benzenetricarboxylic acid chloride is 0.1–0.3 wt%. Step 3) involves contacting the surface of the precursor film treated in step 2) with a 1,3,5-benzenetriformyl chloride solution for at least 120 s to perform interfacial polymerization.
7. A method for preparing a polyamide film material based on G-BSA loose aggregates according to claim 1 or 6, characterized in that, Step 3) The heat treatment temperature is controlled at 50-65 ℃, and the treatment time is 10-20 min.
8. A polyamide film material based on G-BSA loose aggregates prepared by any one of claims 1 to 7, characterized in that, The polyamide membrane material based on G-BSA loose aggregates includes a porous polymer base membrane and a polyamide selective layer located on at least one side of the porous polymer base membrane. The G-BSA loose aggregates are loaded on the side before interfacial polymerization and participate in regulating the local transport of piperazine to the oil phase interface.
9. A polyamide membrane material based on G-BSA loose aggregates according to claim 8, characterized in that, The polyamide membrane material is used for the selective separation of antibiotics and / or inorganic salts.
